Dermatomyositis with intrahepatic cholangiocarcinoma: a case report and data mining based on machine learning - Zhang, Xusheng; Chen, Bendong (Frontiers in Oncology, 2023)
Cancer secondary to dermatomyositis (DM) is defined as paraneoplastic dermatomyositis, which is one of the major subtypes of DM. However, cases of DM with intrahepatic cholangiocarcinoma (ICC) are rarely reported. In the course of our clinical work, we encountered a case of a middle-aged female patient who was diagnosed with DM 7 years, and then diagnosed with ICC, and we would like to share this case.In addition, in order to further investigate the deeper mechanism of ICC associated with DM, we also analyzed the data set related to DM and ICC in the GEO database based on the machine learning methods, and found that PARP12 and MT1M were closely associated with ICC secondary to DM, they are potentially important biomarkers for predicting the occurrence of ICC in patients with DM.